2010
DOI: 10.1017/s1479262110000341
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resources in Trifolium and their utilization in plant breeding

Abstract: Abberton, M. T., Thomas, I. (2011). Genetic resources in Trifolium and their utilization in plant breeding. Plant Genetic Resources: Characterization and Utilization, 9, (1), 38-44. RONO: 03131Clovers (Trifolium species) are a large and widespread genus of legumes. Recent work supports the Mediterranean origin of the genus in the Early Miocene period, and centres of diversity for clovers occur in the Eastern Mediterranean, East Africa and South America. A number of clovers are of agricultural importance as for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Overall, approximately 74,000 accessions of Trifolium are held in global ex situ collections, 53% of which are wild, 14% of which are cultivated and 33% are of unknown improvement status (FAO, 2010, Table 1 (2001) concluded that it contained gaps for (i) cultivars and landraces of red and white clover originating from China, Japan, South America, and South Africa; (ii) obsolete cultivars developed in the USA; (iii) minor-use species; (iv) related wild species; and (v) germplasm distinguished by traits that may be of value to the nutritional supplement or bioremediation industries and that may convey adaptation to abiotic stress or be supportive of sustainable agriculture. Other important questions that need to be examined in order to determine the global ex situ coverage of Trifolium include the extent to which current collections represent an appropriate level of geographical coverage around the globe and to what degree the major collections are sampling independent geographical regions (Abberton and Thomas, 2011). The study of variation in clover germplasm collections based on morphological, phenological, and agronomical characters and molecular markers has resulted in the development of core collections (Kouame and Quesenberry, 1993;Vymyslický et al, 2010Vymyslický et al, , 2012.…”
Section: Crop Clover (Trifolium)mentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, approximately 74,000 accessions of Trifolium are held in global ex situ collections, 53% of which are wild, 14% of which are cultivated and 33% are of unknown improvement status (FAO, 2010, Table 1 (2001) concluded that it contained gaps for (i) cultivars and landraces of red and white clover originating from China, Japan, South America, and South Africa; (ii) obsolete cultivars developed in the USA; (iii) minor-use species; (iv) related wild species; and (v) germplasm distinguished by traits that may be of value to the nutritional supplement or bioremediation industries and that may convey adaptation to abiotic stress or be supportive of sustainable agriculture. Other important questions that need to be examined in order to determine the global ex situ coverage of Trifolium include the extent to which current collections represent an appropriate level of geographical coverage around the globe and to what degree the major collections are sampling independent geographical regions (Abberton and Thomas, 2011). The study of variation in clover germplasm collections based on morphological, phenological, and agronomical characters and molecular markers has resulted in the development of core collections (Kouame and Quesenberry, 1993;Vymyslický et al, 2010Vymyslický et al, , 2012.…”
Section: Crop Clover (Trifolium)mentioning
confidence: 99%
“…White clover develops a dense network of stolons, which enhances grazing tolerance, winter hardiness and persistence. Resistance to pests and diseases, efficient use of water and nutrients, and compatibility with grass are important targets of white clover breeding (Abberton and Thomas, 2011). Breeding programs for white clover are carried out throughout the world: New Zealand (Williams et al, 2007), Australia (Lane et al, 1997;Jahufer et al, 2002), the United States (Taylor, 2008) and the UK (Abberton and Marshall, 2010).…”
Section: Crop Clover (Trifolium)mentioning
confidence: 99%
See 2 more Smart Citations
“…Both ryegrass and white clover have widespread genetic resources in situ, radiating from their Old World centres of diversity (Abberton and Thomas 2011). There are also extensive curated ex situ seed collections, including the Margot Forde Forage Germplasm Centre in New Zealand.…”
Section: Utilising Genetic Resourcesmentioning
confidence: 99%